Comparison of Midline Venous Catheters Versus Peripherally Inserted Central Catheters for Intravenous Therapy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Kumail Mustafa Ali; Hafsa Ahmed; Syeda Fatima Mustafa Zaidi; Talha Khalid; Ahmed Hasan; Urooba Mughal; Ibrahim Zulfiqar Ali; Farida Khan Kakar; Muhammad Hamza; Samina FNU; Rohin Kumar; Suraksha Rani; et al. (Journal of Intensive Care Medicine, 2026)
Background Midline venous catheters (MVCs) have been encouraged as alternatives to peripherally inserted central catheters (PICCs) for intermediate to long-term intravenous therapy. However, randomized controlled trials (RCTs) have reported contradictory findings regarding their comparative safety and resilience. We aim to compare MVCs and PICCs in patients receiving intravenous therapy. Methods PubMed/MEDLINE, Embase, Scopus, and the Cochrane Central databases were searched from inception through March 2025. RCTs comparing MVCs with PICCs in both pediatric and adult population were included. Primary outcomes included total complications, premature catheter removal, and median dwell times. Secondary outcomes included leakage, infiltration, occlusion, catheter-related bloodstream infection, dislodgement, pain, thrombosis, phlebitis, internal malposition, and local infection. Data were pooled using random-effects meta-analysis and reported as risk ratios (RRs) or weighted mean differences (WMDs) with 95% confidence intervals (CIs). Results Seven RCTs including 910 patients (MVC: 454, PICC: 456) met the inclusion criteria. Compared with PICCs, the available RCT evidence suggests that MVCs were associated with a higher risk of overall complications (RR: 2.57; 95% CI: 1.54, 4.31; p = 0.0003), premature catheter removal (RR: 3.91; 95% CI: 1.85, 8.27; p = 0.0004), and shorter median dwell time (WMD: −2.06; 95% CI: −3.18, −0.94; p = 0.0003). MVCs also showed higher point estimates for infiltration (RR: 3.77; 95% CI: 1.08, 13.14; p = 0.04), leakage (RR: 2.91; 95% CI: 1.00, 8.50; p = 0.05), and occlusion (RR: 3.61; 95% CI: 2.13, 6.11; p < 0.00001). No significant differences were reported between the two groups for catheter-related bloodstream infection, thrombosis, phlebitis, dislodgment, internal malposition, or local infection, although the event rates were low and the confidence intervals were wide, limiting certainty. Subgroup analyses were broadly consistent across adult and pediatric populations, although some pediatric-only estimates remained imprecise. Conclusions The available RCT evidence suggests that MVCs are associated with a higher rate of mechanical complications and reduced catheter longevity compared with PICCs. However, low event rates and imprecise estimates limit interpretation of the non-significant findings, especially for the infection-related and thrombosis outcomes, so these results do not establish equivalence between groups and should be interpreted cautiously. Our data suggest that MVCs may be selectively used based on therapy duration, infusate characteristics, and patient-specific factors rather than as routine substitutes for PICCs. Larger randomized trials with longer follow-up are required to validate the findings.